2018
DOI: 10.4143/crt.2017.357
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the National Lung Screening Trial Criteria for Estimation of Lung Cancer in the Korean Population

Abstract: PurposeScreening forlung cancerin high-risk patients using the National Lung Screening Trial (NLST) criteria resulted in a decreased lung cancer-related mortality rate. However, whether these criteria are applicable to the Korean has not been investigated thus far. Therefore, we estimated the utility of the NLST criteria as a screening tool for lung cancer in the Korean population.Materials and MethodsThe total number of newly diagnosed lung cancer cases in 2013 was obtained from the Korea National Statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 16 publications
0
7
0
4
Order By: Relevance
“…Clinico-epidemiological studies based on big data, which aid our understanding of cancer incidence and outcomes, are increasing in Korea 212223. Although large numbers of patients are evaluated,9 comparisons with the general population remain difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Clinico-epidemiological studies based on big data, which aid our understanding of cancer incidence and outcomes, are increasing in Korea 212223. Although large numbers of patients are evaluated,9 comparisons with the general population remain difficult.…”
Section: Discussionmentioning
confidence: 99%
“…In this study population, 17.5% and 18.3% of ever-smokers met the NLST and USPSTF criteria, respectively. In a previous study, approximately 6.9% Korean representative population aged ≥40 years met the NLST criteria (39). In another study, approximately 20% Korean representative population aged 55-74 years met the NLST criteria (40).…”
Section: Discussionmentioning
confidence: 89%
“…In another study, approximately 20% Korean representative population aged 55-74 years met the NLST criteria (40). However, these studies included both never-smokers and smokers (39,40). Considering that 43.9% people aged ≥40 years were ever-smokers (39), the proportion of smokers who met the NLST criteria in Korean representative population would be approximately 15%-16%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the evidence in mortality reduction among the heavy smokers, the question on how to best identify the target population for screening remains open. Multiple studies showed that only approximately 20% to 30% of LC patients would have been eligible for screening with NLST criteria, meaning that 70% to 80% of LC would be missed by screening 27‐36 . LC screening recommendations in the United States are now in the process to be changed to screen a larger proportion of the population that might reduce the number of potentially missed LC.…”
Section: Discussionmentioning
confidence: 99%